Balance concerns in the elderly: Real or imaginary? - Xiao, J.; Hill, Keith; Moore, K.; Williams, S.; Dowson, L.; Borschmann, K.; Dharmage, S. (Elsevier Taiwan LLC., 2012)
Background/Purpose: Older people commonly have concerns about their balance and mobility. This study aimed to identify the prevalence of mild balance dysfunction in community-dwelling older people with self-expressed concerns about balance and to determine factors associated with the presence of mild balance dysfunction. Methods: This was a cross-sectional study in Melbourne, Australia. Participants underwent a comprehensive assessment using clinical and force platform measures to detect mild levels of balance dysfunction. The independent association between potential factors and the presence of mild balance dysfunction was examined by multiple logistic regression while adjusting for confounding effects. Results: A total of 225 participants were recruited. Using a classification algorithm following assessment, 165 participants [73%, 95% confidence interval (CI): 68%–79%] were classified as having mild balance dysfunction. Some of the clinical measures such as the Step Test appeared to be able to discriminate between those with mild balance dysfunction and those without. Factors that were associated with mild balance impairment include: walking velocity [odds ratio (OR) = 0.817, 95% CI: 0.694–0.963); self-report physical activity level (OR = 0.798, 95% CI: 0.649–0.981); and self-reported balance concerns during walking (OR = 2.207, 95% CI: 1.020–4.785).Conclusion: The majority of participants who reported balance concerns had measurable mild balance dysfunction. Early risk identification should target those have lower physical activity level, have slower walking velocity, and express concerns about their balance during walking. Further research should investigate the utility of the simple clinical measures in isolation to classify risk of mild balance dysfunction. Health professionals should refer older people who report balance-related concerns to appropriate investigators and interventionists.